Revealing Gender Relations in Arab Society in the Film Barakah Yuqâbil Barakah Through a Literary Sociology Perspective - Asrina, Asrina; Army, Putri Athifah; Al Barqy, Muhammad Musa (Jurusan Bahasa dan Sastra Arab Universitas Islam Negeri Alauddin Makassar, 2024)
يركز هذا البحث على مشكلة أنماط العلاقة بين الجنسين الموجودة في فيلم بركة يقابل بركة. وتعتبر مسألة العلاقة بين الجنسين في هذا الفيلم مثيرة للاهتمام ومهمة للدراسة لأن هذا الفيلم يستكشف عن العلاقة بين الجنسين ضمن الإطار الثقافي للمجتمع السعودي الذي يتطابق مع المجتمع الأبوي، ويقوم على الشريعة الإسلامية، ويحد بشكل كبير من مساحة حركة المرأة. طريقة البحث المستخدمة في هذا البحث هو الوصفي التحليلي بمنهج علم الاجتماع الأدبي وهو علم الظواهر الاجتماعية. ومصدر البيانات الأساسي هو فيلم بركة يقابل بركة لمحمود صباغ. تظهر نتائج البحث أن هناك عدة أشكال للعلاققة بين الجنسين في هذا الفيلم. الشكل الأول هو الهيمنة في العلاقة بين الجنسين، والشكل الثاني هو التبعية في العلاقة بين الجنسين، والشكل الثالث هو العلاقة المتساوية بين الجنسين. ومن جميع أشكال العلاقة الموجودة بين الجنسين في هذا الفيلم، يمكن أن يستنتج أن هناك مشاكل كبيرة في العلاقة بين المرأة والرجل في المجتمع العربي، وكانت العلاقة بين الجنسين في الماضي تعتبر أفضل مقارنة بالمجتمع العربي اليوم، وأن النظام القائم لا يدعم إقامة علاقة جيدة بين الجنسين، وأن هناك شرعية دينية فيما يتعلق بالعلاقة بين الجنسين. Abstract This article focuses on the patterns of gender relations depicted in the film Barakah Yuqâbil Barakah. The issue of gender relations in this film is intriguing and significant for research because it explores gender relations within the cultural framework of Saudi society, which aligns with a patriarchal system, is based on Islamic Sharia, and significantly restricts women's mobility. The research method used in this article is descriptive-analytical, employing the literary sociology approach, which is a study of social phenomena. The primary data source is the film Barakah Yuqâbil Barakah by Mahmoud Sabbagh. The research findings reveal several forms of gender relations in this film. The first form is dominance in the relationship between the sexes, the second form is dependency in gender relations, and the third form is equal gender relations. Among all the forms of gender relations depicted in this film, it can be concluded that there are significant issues in male-female relations in Arab society. Gender relations in the past were considered better compared to contemporary Arab society, and the existing system does not support the establishment of healthy gender relations. Additionally, there is a religious legitimacy concerning gender relations.